Are biomechanics during gait associated with the structural disease onset and progression of lower limb osteoarthritis? A systematic review and meta-analysis. Issue 3 (March 2022) - D'Souza, N.; Charlton, J.; Grayson, J.; Kobayashi, S.; Hutchison, L.; Hunt, M.; Simic, M.
Summary: Objective: To evaluate if gait biomechanics are associated with increased risk of structurally diagnosed disease onset or progression of lower limb osteoarthritis (OA). Method: A systematic review of Medline and Embase was conducted from inception to July 2021. Two reviewers independently screened records, extracted data and assessed risk of bias. Included studies reported gait biomechanics at baseline, and either structural imaging or joint replacement occurrence in the lower limb at follow-up. The primary outcome was the Odds Ratio (OR) (95% confidence interval (CI)) of the association between biomechanics and structural OA outcomes with data pooled for meta-analysis. Results: Twenty-three studies reporting 25 different biomechanical metrics and 11 OA imaging outcomes were included (quality scores ranged 12–20/21). Twenty studies investigated knee OA progression; three studies investigated knee OA onset. Two studies investigated hip OA progression. 91% of studies reported a significant association between at least one biomechanical variable and OA onset or progression. There was an association between frontal plane biomechanics with medial tibiofemoral and hip OA progression and sagittal plane biomechanics with patellofemoral OA progression. Meta-analyses demonstrated increased odds of medial tibiofemoral OA progression with greater baseline peak knee adduction moment (KAM) (OR: 1.88 [95%CI: 1.08, 3.29]) and varus thrust presence (OR: 1.97 [95%CI: 1.32, 2.96]). Conclusion: Evidence suggests that certain gait biomechanics are associated with an increased odds of OA onset and progression in the knee, and progression in the hip. Registration number: PROSPERO CRD42019133920